Diagnóstico de la carga mental de los profesores de la carrera de Administración Pública de la ESPAM MFL - Zambrano Rivera, Arianna Dalía (2016)
The mission of teachers at Public Administration School in the ESPAM MFL is vital for the formation of future professionals in the country; however, its work is not exclusive related to classes dictation but also the countless activities such as tutoring, academic redesign, thesis, among others that require a high degree of mental effort to fulfill its activities, therefore, it is necessary to measure or assess the level of mental effort to which they are exposed. In research it is used to guide the methodology proposed by Carvalho: Physiologically, testing blood pressure, level of blood oxygenation, heart rate and cholesterol; psychophysiological: simple time reaction and complex time reaction; and psychological: subjective feeling of fatigue. The fusion of these elements is considered optimal because it mixes both objective aspects such as physiological reactions, alertness and subjective as allowing test more accurately determine if the mental load is present on teachers. Through various evidence presented demonstrated that full-time teachers of the Public Administration School have a high level of mental load and between the impact associated with this situation are: Frustration, physical and mental fatigue, irritability, affection in their relationships, headaches and migraine, a low level of attention in the last hours of classes.